Procedures and Methodologies for the Control and Improvement of Energy-Environmental Quality in Construction - Nastasi, Benedetto; Mancini, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue aims at providing the state-of-the-art on procedures and methodologies developed to improve energy and environmental performance through building renovation. We are greatly thankful to our colleagues building physics experts, building technology researchers, and urban environment scholars who contributed to this Special Issue, for sharing their original works in the field.